(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article discusses the historical development of the firs ironworks that were founded in Mexico in the nineteenth century. Special emphasis is plaed on the evolution of the ironworks in the company named Nuestra Señora de Guadalupe, established by the mineralogist Andres Manuel del Rio in Coalcomán in 1805 and the one in Piedras Azules built in Durango in 1826. Also looks at other foundries that were established in the present states of Jalisco, Guanajuato, Hidalgo, Morelos and Oaxaca. The leitmotif of the cases studied is the continuities and changes in technology that were used in foundry systems and benefit of ferrous materials. It also addresses the use of iron in the development of agricultural tools for the extraction of minerals, incluiding the mills that were used in sugar mills.